High antiviral activity of NS5A inhibitor ABT‐530 with paritaprevir/ritonavir and ribavirin against hepatitis C virus genotype 3 infection. (3rd February 2016) - Poordad, Fred; Landis, Charles S.; Asatryan, Armen; Jackson, Daniel F.; Ng, Teresa I.; Fu, Bo; Lin, Chih‐Wei; Yao, Betty; Kort, Jens
Abstract: Background & Aims: ABT‐530 is a next‐generation hepatitis C virus (HCV) NS5A inhibitor with potent pangenotypic antiviral activity in vitro . Paritaprevir is an NS3/4A protease inhibitor codosed with ritonavir that displays in vitro activity against HCV genotypes 1–4 and 6. Methods: Efficacy, pharmacokinetics and safety of ABT‐530 with paritaprevir/ritonavir and ribavirin were evaluated in this phase 2, open‐label, multicentre study in treatment‐naïve non‐cirrhotic patients with genotype 3 infection. Ten patients, all genotype 3a, received 120 mg ABT‐530 and 150/100 mg paritaprevir/ritonavir once daily with ribavirin for 12 weeks. Results: Nine (90%) patients achieved a sustained virological response at post‐treatment weeks 12 and 24. One patient experienced virological failure at treatment week 6. Sequence analyses for HCV variants in samples from this patient identified A166S in NS3 at baseline and after breakthrough, as well as A30K at baseline and linked S24F+M28K+A30K variants in NS5A after breakthrough. Neither genotype 3 NS3 A166S nor NS5A A30K variant confers any resistance to paritaprevir or ABT‐530 respectively. However, genotype 3 NS5A S24F+M28K+A30K‐linked variant confers a >5000‐fold increase in ABT‐530 EC50 relative to that of the wild‐type replicon. This patient's ABT‐530 exposure was comparable to the cohort, while paritaprevir and ritonavir exposures were the lowest of all patients. No serious or severe adverse events and adverse events leading to early discontinuation were reported. Conclusions: Results from this study show that ABT‐530 holds promise as part of a direct‐acting antiviral treatment regimen for HCV genotype 3 infection.